2015
DOI: 10.1007/s40843-015-0059-9
|View full text |Cite
|
Sign up to set email alerts
|

Altering the response of intracellular reactive oxygen to magnetic nanoparticles using ultrasound and microbubbles

Abstract: Engineered iron oxide magnetic nanoparticles (MNPs) are one of the most promising tools in nanomedicine-based diagnostics and therapy. However, increasing evidence suggests that their specific delivery efficiency and potential long-term cytotoxicity remain a great concern. In this study, using 12 nm γ-Fe2O3 MNPs, we investigated three types of uptake pathways for MNPs into HepG2 cells: (1) a conventional incubation endocytic pathway; (2) MNPs co-administrated with microbubbles under ultrasound exposure; and (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…23 The mechanisms associated with ultrasound-assisted internalization of nanoparticles have suggested that sonoporation leads to noninternalizing uptake routes, reducing oxidative stress and minimizing long-term cytotoxicity of nanoparticles in healthy cells. 24 Therefore, ultrasound provides a promising outlook in cancer treatment by improving drug/nanoparticle delivery, yet its incorporation as an integrated component in drug/MFH combination treatments has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…23 The mechanisms associated with ultrasound-assisted internalization of nanoparticles have suggested that sonoporation leads to noninternalizing uptake routes, reducing oxidative stress and minimizing long-term cytotoxicity of nanoparticles in healthy cells. 24 Therefore, ultrasound provides a promising outlook in cancer treatment by improving drug/nanoparticle delivery, yet its incorporation as an integrated component in drug/MFH combination treatments has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of sinalpultide in suspension and microbubble was 0.1 mg/mL, and the ultrasound parameters were set as follows: frequency 0.5 MHz; intervention time 40 seconds; pressure 24.6 kPa. 15 After 24 hours incubation, cells were washed twice with PBS, MTT reagent was added to each well and co-incubated with cells for 4 hours at 37°C. The cell activity was determined by measuring the changes in absorbance at 490 nm using a microplate reader.…”
Section: Methodsmentioning
confidence: 99%
“…However, subsequent studies have revealed that MNPs have pH-dependent peroxidase and catalase activities like those of certain enzymes. Chen et al [111,112] reported that iron oxide nanoparticles can catalyze H2O2 to produce the hydroxyl radical (·OH) under acidic conditions, and the hydroxyl radical is then able to oxidize a variety of organic molecules. That is, the MNPs have peroxidase-like activity.…”
Section: Magnetic Nanoparticles Themselves As a Drug Delivery Systemmentioning
confidence: 99%